INVESTIGATION OF SOYBEAN PROCESSING BY FORCING – EXTRACTION METHOD - SALEBA, LUDMILA; SARIBEKOVA, DIANA; MELEKHOVA, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The study of the influence of physicochemical parameters of different sorts of soybean on the extraction of oil in soybean processing, as were as determining the quality of soybean products – petal, meal and oil. Soybean seed samples of three sorts were selected for the study: Mriya, Skelya and Ukrainka, of different humidity and degree of contamination. The Perten DA 7250 infrared analyzer and physicochemical methods in accordance with DSTU were used to determine the quality indicators of soybean seeds. Skelya sort was noted as more oily (20.36%), and Ukrainka sort as more protein (38.49%), the mass fraction of fiber in the samples is from 5.9 to 6.5%. The scheme of soybean processing by the method of forcing – extraction with hexane at the enterprise of «Tavria Agroinvest» was used. Soybean oil is extracted according to the technological regime of the enterprise. After the process of extraction and distillation of the solvent in the evaporator tank, unrefined soybean oil and soybean meal are obtained. According to the scheme of the extraction process, the quality of the final product will depend on the degree of grinding of raw materials and the quality of the petal. Organoleptic and physicochemical parameters of unrefined soybean oil and soybean meal obtained at «Tavria Agroinvest» from three sorts of soybean seeds were determined. It is shown that from moist materials (18.5%) is obtained oil with higher acid and peroxide numbers. The iodine number and cloud point of soybean oil of this sample are also higher than those obtained for dry seeds. The quality indicators of soybean meal for the studied soybean seed sorts were obtained. Mass fraction of crude protein in terms of absolute dry matter is the largest for the Skelya sort and is 46.2%. Soybean meal sort Mriya is less purified from moisture and crude fat, and its high acid number can shorten the shelf life.